The impact of imports from China on African textile exports - Yong He (Journal of African Trade, 2020)
This study uses Comtrade trade data covering 1990-2017, 14 textile subsectors, and 53 African countries with their main trade partners to evaluate Chinese trade impacts on African textile exports over three subperiods at the sector level. It finds that, although textile imports from China had a significant positive impact during the first period, this effect disappeared in the second period. From 2009 to 2017, the impact became significantly negative. I explain these results by arguing that Chinese products exert both intermediate goods and crowding-out effects on African local producers. During the first period, the intermediate goods effect exceeded the crowding-out effect, and helped to strengthen African textile production and exportation. Over time, however, the net crowding-out effect was increasing. In the last period, imports from China reduced Africa's exports. This study, thus, raises a concern about African "premature deindustrialization", presumably as a consequence of the continent's trade with China.
Keywords: C23; F14; O19; 330; African textile exports; textile imports from China; comparative advantage; crowding-out effect; intermediate goods effect; Textilien; Import; Export; Verdrängungseffekt; Textilindustrie; Afrikanisch; Afrika; China